Systematic review and meta-analysis of the prevalence and determinants of exclusive breastfeeding in the first six months of life in Ghana - Shamsudeen Mohammed; Ibrahim Yakubu; Abdul-Ganiyu Fuseini; Abdul-Malik Abdulai; Yakubu H. Yakubu (BMC, 2023)
Abstract Background Exclusive breastfeeding is a public health priority in sub-Saharan Africa. However, systematic reviews on its determinants in Ghana remain scarce. Therefore, we systematically reviewed the prevalence and determinants of exclusive breastfeeding in children 0-6 months in Ghana. Methods We conducted systematic searches in Embase, Medline, and Africa-Wide Information from the databases' inception until February 2021 for studies that assessed the prevalence and determinants of exclusive breastfeeding in children 0-6 months in Ghana. Random-effects meta-analysis was used to estimate the pooled prevalence of exclusive breastfeeding and narrative synthesis to summarise the determinants. We calculated the proportion of total variability that was due to between study heterogeneity using I² statistics, and Egger's test assessed publication bias. The review is registered with PROSPERO, CRD42021278019. Results Out of the 258 articles identified, 24 met the inclusion criteria. Most of the included studies were cross-sectional and were published between 2005 and 2021. The pooled prevalence of exclusive breastfeeding (EBF) among children 0-6 months in Ghana was 50% (95%CI 41.0-60.0%). The prevalence was higher in rural areas (54%) than in urban areas (44%). Several factors were identified as facilitators of EBF, including older maternal age, self-employment, unemployment, living in a large house, being a house owner, giving birth in a health facility, non-caesarean delivery, adequate antenatal attendance, counselling services, participation in support groups, adequate knowledge about EBF, positive attitude towards EBF, and higher maternal education among rural dwellers. Additionally, having an average birthweight facilitated EBF. Barriers to EBF were also identified, including higher maternal education among urban dwellers, less than three months of maternity leave, maternal HIV-positive status, the experience of partner violence, lack of access to radio, inadequate breastmilk production, lack of family support, having a partner who wants more children, counselling on complementary feeding, healthcare worker recommendation of complementary feed, single marital status, and infant admission to neonatal intensive care units. Conclusion In Ghana, EBF rates are low, with only about half of all children aged 0-6 months breastfed exclusively. A multi-dimensional approach is required to tackle the diverse sociodemographic, obstetric, and infant-related issues that hinder EBF practice in Ghana.